2007
DOI: 10.1021/jm070255o
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamoyl Derivatives of 7α-Aminomethyl-6,14-endo-ethanotetrahydrothebaine and 7α-Aminomethyl-6,14-endo-ethanotetrahydrooripavine and Related Opioid Ligands

Abstract: A new series of ligands has been synthesized where the cinnamoyl group of the 14-cinnamoylamino morphinones has been introduced to the 7α-substituent of the 6,14-bridged oripavine series. In vitro the compounds were mostly low efficacy partial agonists or antagonists with some selectivity for the mu opioid receptor, with evidence of mu efficacy in vivo. The similarity in SAR between these 6,14-bridged oripavines and the 14-cinnamoylamino series suggests a similar mode of interaction with the mu opioid receptor. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…These compounds engendered primarily saline-lever responding up to doses that either significantly reduced response rates or induced untoward side effects (e.g., convulsions). We are not aware of any other studies that have administered these particular opioid receptor agonists to ethanol discriminating subjects, however, we selected these compounds based on their known selectivity and/or efficacy profiles at mu and/or delta opioid receptors (e.g., fentanyl: mu opioid receptor full agonist, ~ 100- to 250-fold selective for mu vs. delta, Emmerson et al, 1994; Jagerovic et al, 2002; buprenorphine: mu opioid receptor partial agonist, ~ 3- to 15-fold selective for mu vs. delta, and kappa opioid receptor antagonist, Rennison et al, 2007; Spagnolo et al, 2008; SNC 80: delta opioid receptor full agonist, ~ 800- to 900-fold selective for delta vs. mu, Knapp et al, 1996; Codd et al, 2009; SNC 162: partial agonist, > 1000-fold selective for delta vs. mu, Knapp et al, 1996). Our results, however, are in general concordance with other studies reporting a lack of substitution of the mu opioid receptor agonist morphine for the discriminative stimulus effects of ethanol in monkeys and rats (Winter, 1975; York and Bush, 1982; Bowen et al, 1997; Kosten et al, 1999; Platt et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These compounds engendered primarily saline-lever responding up to doses that either significantly reduced response rates or induced untoward side effects (e.g., convulsions). We are not aware of any other studies that have administered these particular opioid receptor agonists to ethanol discriminating subjects, however, we selected these compounds based on their known selectivity and/or efficacy profiles at mu and/or delta opioid receptors (e.g., fentanyl: mu opioid receptor full agonist, ~ 100- to 250-fold selective for mu vs. delta, Emmerson et al, 1994; Jagerovic et al, 2002; buprenorphine: mu opioid receptor partial agonist, ~ 3- to 15-fold selective for mu vs. delta, and kappa opioid receptor antagonist, Rennison et al, 2007; Spagnolo et al, 2008; SNC 80: delta opioid receptor full agonist, ~ 800- to 900-fold selective for delta vs. mu, Knapp et al, 1996; Codd et al, 2009; SNC 162: partial agonist, > 1000-fold selective for delta vs. mu, Knapp et al, 1996). Our results, however, are in general concordance with other studies reporting a lack of substitution of the mu opioid receptor agonist morphine for the discriminative stimulus effects of ethanol in monkeys and rats (Winter, 1975; York and Bush, 1982; Bowen et al, 1997; Kosten et al, 1999; Platt et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several structure-activity relationship (SAR) studies have shown that the 6,14-bridged oripavines with a cyclopropylmethyl group at N 17 , such as diprenorphine, buprenorphine, and naltrexone, might possess some morphine-antagonist characteristics. Replacing this group with a methyl group has been found to greatly increase the efficacy of compounds, particularly at the µ-and κ-opioid receptors [11,12] . We also considered that the mixed ORL1/µ-opioid receptor activity of 030418 may have an attractive profile for the treatment of pain and addiction, similar to SR16435 and buprenorphine [32,33] .…”
Section: Discussionmentioning
confidence: 99%
“…Many compounds obtained from the structural modification of buprenorphine have also been extensively developed [6,11,12] . Inspired by these reports, N-cyclopropylmethyl-7α-[(R)-1-hydroxy-1-methyl-3-(thien-3-yl)-propyl]-6,14-endo-ethanotetrahydronororipavine (thienorphine, Figure 1) was synthesized in our institute [13] .…”
Section: Introductionmentioning
confidence: 99%
“…36 A solution of oxime 6 (0.58 g; 2.4 mmol) in anhydrous THF (10 mL) was added dropwise to a suspension of LiAlH 4 (0.23 g, 6.0 mmol) in the same solvent (10 mL). The resulting mixture was stirred for 24 h at room temperature.…”
Section: Reduction Of Oxime 6 To Aminementioning
confidence: 99%